Credibility in evaluating on-line wear-depth detection of self-lubricating spherical plain bearings. (August 2016) - Li, Wei; Hu, Zhanqi; Yang, Yulin; Qi, Xiaowen; Zhou, Haili
The wear-depth detecting precision of self-lubricating spherical plain bearings directly affects the accuracy of evaluating on the tribological properties of bearings. However, because of the varying environmental factors, the detecting errors in the on-line experimental data of the wear depth affect the accuracy of the detecting data. In this article, we come up with the definition of the credibility of the on-line wear-depth detection of spherical plain bearings on the similarity between the on-line wear depth data and the conventional true value of the wear depth and present two evaluating indexes of the credibility of the on-line wear-depth detection according to the features of spherical plain bearing testers—the small sample, the dynamic measurement, and the complex operating conditions with much interference. The two indexes are the index I, the similarity between the on-line detecting curve and the off-line detecting curve using the algorithm of the discrete Fréchet distance, and the index II, the fluctuating amplitude of the on-line wear-depth detecting curve through adopting the computing method of the profile arithmetic average error of the surface roughness. Finally, we use the above evaluating indexes to analyze the comparative study of the detecting credibility for the same tester of spherical plain bearings before and after the thermal error compensation.